The Effect of Freeze-Thaw Damage on Corrosion in Reinforced Concrete - Xiao-Chun Lu; Bin Guan; Bo-Fu Chen; Xin Zhang; Bo-bo Xiong (Advances in Materials Science and Engineering)
The existing studies of the corrosion of reinforced concrete have mainly focused on the interface area and chemical ion erosion, ignoring the specific service environment of the reinforced concrete. In this study, the effect of freeze-thaw damage was investigated via corrosion experiments under different freeze-thaw cycle conditions. Steel reinforcement corrosion mass, ultimate pull-out force, corrosion rate, and bond slippage were chosen as characteristic parameters in the experiments, and scanning electron microscopy (SEM) analysis was used to explain the mechanism of action of freeze-thaw damage on corrosion. The results showed that, under identical corrosion conditions, the mass of steel reinforcement corrosion and corrosion rate increased by 39.6% and 39.7% when comparing 200 freeze-thaw cycles to 0 cycles, respectively. The ultimate pull-out force and bond slippage after 200 freeze-thaw cycles decreased by 73% and 31%, respectively, compared with 0 freeze-thaw cycles. In addition, SEM analysis indicated that microstructure damage caused by freeze-thaw cycles accelerated the corrosion reaction and decreased cementitious properties, leading to decreasing ultimate pull-out force and bond slippage. The effect of freeze-thaw cycles and steel reinforcement corrosion on the macro mechanical properties of concrete is not a simple superposition.